Fallowing of selected arable fields in a farmland mosaic affects processes on landscape level: a case study of small mammal communities - Kozakiewicz, Michał; Radzikowski, Jacek; Ostrowski, Marek; Kozakiewicz, Anna (Ecological Questions, 2013)
In 2008 on six 1-ha plots the structure and species diversity of small mammal community inhabiting a narrow belt of coastal zone of the Łuknajno Lake (Masurian Lake District, North-East of Poland) were studied. The results obtained were compared with the results of similar studies carried out in the same area in 1981, when still intensive agricultural activities were present around the lake (abandoned in 1991 by leaving the agricultural fields fallow). In comparison with 1981, a decrease in the number of species inhabiting the fringe of the lake was discovered, as well as some significant changes in the domination structure of the community. Currently, the dominant forest species - the bank vole Myodes glareolus (Schreber 1780) and the yellow-necked mouse Apodemus flavicollis (Melchior 1834) - replaced the most numerous in 1981 - the striped field mouse Apodemus agrarius (Pallas 1771). Taking into consideration the fact that environmental conditions at the coastal zone have not changed, it was suggested that the changes in the community of small mammals were caused by setting aside arable lands around the lake. The results obtained lead to the conclusion that the range of the ecological effects of local changes in the landscape mosaic may include an area much larger than the one directly affected by these changes. They constitute the basis for a discussion on the relationship between various elements of environmental mosaic in heterogeneous landscape.